Development of the marsupial shoulder girdle complex: a case study in Monodelphis domestica. Issue 1 (20th January 2013) - Hübler, Merla; Molineaux, Anna C.; Keyte, Anna; Schecker, Teresa; Sears, Karen E.
SUMMARY During their embryogenesis, marsupials transiently develop a unique structure, the shoulder arch, which provides the structural support and muscle‐attachments necessary for the newborn's crawl to the teat. One of the most pronounced and functionally important aspects of the shoulder arch is an enlarged coracoid. The goal of this study is to determine the molecular basis of shoulder arch formation in marsupials. To achieve this goal, this study investigates the relative expression of several genes with known roles in shoulder girdle morphogenesis in a marsupial—the opossum, Monodelphis domestica—and a placental, the mouse, Mus musculus. Results indicate that Hoxc6, a gene involved in coracoid patterning, is expressed for a longer period of time and at higher levels in opossum relative to mouse. Functional manipulation suggests that these differences in Hoxc6 expression are independent of documented differences in retinoic acid signaling in opossum and mouse forelimbs. Results also indicate that Emx2, a gene involved in scapular blade condensation, is upregulated in opossum relative to mouse. However, several other genes involved in shoulder girdle patterning (e.g., Gli3, Pax1, Pbx1, Tbx15) are comparably expressed in these species. These findings suggest that the upregulation of Hoxc6 and Emx2 occurs through independent genetic modifications in opossum relative to mouse. In summary, this study documents a correlation between gene expression and the divergent shoulder girdle morphogenesis of marsupial (i.e., opossum) and placental (i.e., mouse) mammals, and thereby provides a foundation for future research into the genetic basis of shoulder girdle morphogenesis in marsupials. Furthermore, this study supports the hypothesis that the mammalian shoulder girdle is a highly modular structure whose elements are relatively free to evolve independently.